Morphometric Changes in Talus of Club Foot A Gross Observation in Human Foetuses - Fazal-ur-Rehman (Sociedad Chilena de Anatomía, 2012)
Both the feet of six human foetuses of different age groups having unilateral club feet, were dissected for morphological study. Six morphometric parameters considered for comparing gross anatomical changes in normal and deformed feet, were 1-Maximum length of the talus, 2-Longitudinal dimension of head of talus, 3-Anterior trochlear breadth, 4-Maximum medial talar height, 5-Talar neck and calcaneal angle, 6-Talocalcaneal angle. All the foetuses with congenital club feet have almost similar deformity of foot skeleton. The gross anomalies observed were the smaller size of club foot talus and increased medial and planter deviation of a stunted, misshapen head and neck region. A medial plantar subluxation of the navicular bone with a consequent deformity of the articular facets of the talar head was also observed. Uniformity and consistency of anatomical abnormalities were striking features in present study.